Private and public nursing schools in Karachi, Pakistan - Amber Hussain Sayani; Dilshad Begum Maqsad Jan (International Journal of Endorsing Health Science Research, 2015)
Nursing is a field which is directly affecting patients’ quality of life. For this, there is a dire need to bring competent and professional nurses who pass on the dignity of their nursing profession. This heavy responsibility to produce such competent and professional nurses lies on educational institutions and nursing schools. Educational institutions play a vital role in offering a standard of education for future nurses. Hence, it is essential or educational institutions of nursing to undergo a quality assurance process in order to monitor their efficiency and standards of nursing education. While comparing two nursing institutions, we found some issues and challenges in both private and public institutions. Public institution has the resources, but poor strategic planning for initiating the new programs; while private institute cannot expand their programs due to lack of resources. Private institute has a better education system as compared to the public institute despite of limited possessions.